Nutrition for Health and Fitness: Fiber in Your Diet - Linda B. Bobroff (EDIS, 2012)
Fiber has many names, such as dietary fiber, total fiber, or just plain fiber. Eating foods that contain fiber is good for your health. This revised 6-page fact sheet provides tips on how to include foods with fiber in your diet. Written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, September 2012.